Making Sense of Proprioception by Bibliometric Research - Kevser Sevik Kacmaz (Brain and Behavior, 2025)
ABSTRACT Background Proprioception is one of the most significant factors in balance, stability, fine movements, coordination, and injury prevention. Proprioception research helps clarify how the nervous system integrates sensory inputs to plan and execute movements. Bibliometric analyses offer a systematic and comprehensive understanding of a field's structure, evolution, trends, research clusters, and gaps, laying a scientific foundation for future research. This study employs bibliometric analysis to provide a panoramic view of proprioception research and to identify its thematic structure, evolution, production, and impact. Methods A total of 4506 original studies from 1979 to 2024 were extracted from the WoS. Using the Bibliometrix application in RStudio, a bibliometric analysis examined scientific performance, production, citation impact, research trends, developments, and the conceptual framework related to proprioception research. The Biblioshiny application performed the scientific mapping. Results Proprioception research has increased linearly. The most influential article was Sensorimotor System Measurement Techniques, published in the Journal of Athletic Training, with 455 citations. Uwe Proske was the most influential author, with an h‐index of 20 in proprioception. The literature utilized 6797 keywords. Of these, 29% was proprioception, 4% joint position sense, and 4% rehabilitation. Keyword trends showed a shift toward rehabilitation and neurophysiology, with terms such as “rehabilitation,” “balance,” and “stroke” becoming more prevalent. However, an emerging interest in psychophysics, which investigates the interaction between proprioception and sensory perception, is also evident. This theme offers significant opportunities for future research. The USA leads in productivity, contributing 57.70% of the total publications, followed by Canada with 19.32%, and the UK with 18.28%. Conclusions The results indicate a significant upward trend in research output, highlighting the increasing importance of proprioception in clinical and research settings. The findings emphasize several gaps in current proprioception research, including the need for greater interdisciplinary collaboration, particularly with neuroprosthetics and AI‐driven proprioceptive modeling. Furthermore, geographical diversity in research, particularly from underrepresented regions, is critical for comprehensively understanding proprioception across diverse populations. This study provides actionable information for researchers, clinicians, and policymakers. It urges future investigations to address these gaps and explore innovative approaches to enhance proprioception‐based therapies and technologies.